Company towns of the Bat'a Concern. History - cases - architecture. - (:unkn) unknown (Steiner, 2013)
During the interwar years, the footwear industry was confronted with similarly revolutionary changes and processes to those in the automobile industry which tend to be associated with the name of Henry Ford. Their major vehicle became the originally Czechoslovak enterprise of the Bat'a siblings, which, during the first decades of the twentieth century, grew into a gigantic concern with global reach. Seventeen researchers from Europe and North America trace the fascinating story of the Bat'a concern, a substantive chapter of which from the end of the 1920s became the establishment of company towns. From various perspectives, they focus their attention on this unique model of industrial organization which was discussed widely in its time and which in retrospect can be considered one of the true pinnacles of private capitalist urban planning in the first half of the twentieth century.
Keywords: Wohnsiedlung; Siedlungsgeschichte; Architektur; Unternehmensgeschichte; Werksiedlung